Belarus – Latvia: achievements and difficulties in bilateral cooperation (1992–2017) - Shadurski, Victor G. (Journal of the Belarusian State University. International Relations, 2018)
The present article is devoted to the analysis of the Belarusian-Latvian relations during the period after the two countries gained independence. The author came to the conclusion that the main obstacle to expanding bilateral cooperation is the opposite of geopolitical aspirations of Minsk and Riga and, as a consequence, a different attitude of the neighbouring countries to the problem of human rights and historical policy. It is unlikely that the existing disagreements can be eliminated in the coming years. However, such advantages as the geographic proximity of the two countries, the cultural and historical proximity of the Belarusians and Latvians are a favourable factor for establishing effective interaction in the economic sphere, contacts at the level of regions and cities. A great capacity for cooperation exists in the Belarusian-Latvian border area. The article contains an attempt to define “points of growth” in bilateral relations, as well as to identify problems that can be eliminated without serious financial costs.